Web-Based LEO Satellite Orbit Design Application: A Comparative Analysis of Analytical and Numerical Propagation Methods - Wedagama , I Dewa Made Raviandra; Setiawan, Dhoni Putra; Edwar, Edwar (eProceedings of Engineering, 2025)
Low Earth Orbit (LEO) missions increasingly re- quire design tools that are both accessible and sufficiently accurate for early trade studies. This paper presents a browser-native LEO Satellite Orbit Design Application that combines analytical j2 averaged propagation, constellation synthesis (Train and Walker–Delta), footprint coverage from spherical geometry, and narrowband link-budget calculations within interactive 2D/3D visualizations. The computational core is implemented in double- precision JavaScript and validated against NASA GMAT (RK4) and closed-form theory. Over a 60 min propagation at ∼1,000 km circular equatorial orbit, the analytical model exhibits a 24.4–40.2 km position-error envelope (RMSE 31.8 km), reflecting short period terms captured by GMAT but intentionally averaged for real-time performance. Constellation placement is exact; at 2,000 km with 60◦ beamwidth, footprint radius error is 0.05 km (0.004%). Uplink/downlink C/N and margins match manual calculations and imply ≈1.12 Gbps Shannon capacity at 100 MHz. Ground-station access scheduling reproduces pass counts and timing (11 passes/day; mean 8.55 min; first access 40.05 min). We conclude that analytical ????2 propagation offers accuracy adequate for education and early design with instant, browser-only work- flows, while high-fidelity numerical tools remain appropriate for final verification and operations. Keywords——LEO satellites; analytical propagation; J2 per- turbation; web application; constellation design; link budget